Uporaba zvočne jakosti in preskusne načinovne analize za določitev hrupa dizelskega motorja - Petrović, Predrag (Strojniški vestnik, 2007)
The internal combustion engine represents a multi-exciting source of vibrationand noise that originates from its assemblies, and whose energy of operation is transformed into sound-wave energy. The energy absorbed in the engine's structure excites the natural modal oscillations of the larger engine parts (cylinder block, oil sump, cylinder head, etc.), through whose surfaces the sound is radiated. To determine the level of emitted sound in individual areas of the engine at various running speeds, detailed research was carried out at Industrija motora Rakovica of Belgrade using experimental modal analyses and sound-intensity measurements. In this way a correlation wasmade between the natural modal frequencies and the emitted sound from particular external areas of the diesel engine. Some of the results obtained in the course of these investigations are presented in this paper.
Keywords: dizelski motorji; hrup; zvok; jakost; modalna analiza